Diseño de un plan de mejoramiento turístico hacia el aprovechamiento de los recursos naturales y sociales de la comunidad La Toglla-parroquia Guangopolo - Gómez Guallichico, Daniela Carolina (2015)
This document contains a desing of touristic improvement plain that allows the correct use of natural and social resources in La Togglla community, ubicated in the Guangopolo town. The research objective is create the supported use of touristic activities, protecting the natural resources, but it is provided business opportunities and improvement the life conditions of the local people. To these, it is presents the theorical bases about the popular and solidarity economy, its definition, importance and legal bases, applied the smarter concept for development the central study argument. Also, it is presents the basics categories of communitary tourism and its management, providing a guide about the possibilities in La Toglla community. The evidences of the direct research exhibit the present situation in the study site, watching the community history, with its demographic basics data, its touristic attractive and the weakness identifies in the administration, finance, operative, marketing and human resources areas. The proposal is manage to improve the present situation in the identifies areas, with the activities formalization, designing a structure with the functions for the human resources that works in the Community Tourism Center “La Toglla” (local people and tourists), the community hostel construction and the touristic attractive adaptation, between other important activities.